The Tyranny of Purpose: Religion and Biotechnology in Ishiguro’s Never Let Me Go - Tsao, Tiffany (Literature and theology, 2012)
Critics and reviewers of Kazuo Ishiguro’s novel Never Let Me Go (2005) have often compared it to Mary Shelley’s Frankenstein (1818), but have failed to explore their similarities in a more in-depth manner. A detailed and sustained comparison of the two novels reveals further connections between Ishiguro’s novel and Milton’s Paradise Lost (1667), yielding surprising insight into the deeply theological nature of Never Let Me Go and what it has to say about religious life and biotechnological creation. As it turns out, we may be sorely mistaken about the very features of religion and biotechnology that we tend to perceive as merits: namely, religion’s ability to provide its adherents with a sense of purpose, and the benevolent purposes for which biotechnological research is undertaken.